Telomerase Variants in Patients with Cirrhosis Awaiting Liver Transplantation. Issue 6 (9th April 2019) - Chiu, Victor; Hogen, Rachel; Sher, Linda; Wadé, Niquelle; Conti, David; Martynova, Anastasia; Li, Hongtao; Liang, Gangning; O'Connell, Casey
Abstract : Telomeres are repetitive DNA sequences that protect the ends of linear chromosomes, and they are maintained by a ribonucleoprotein complex called telomerase. Variants in genes encoding for telomerase components have been associated with a spectrum of disease in the lung, skin, bone marrow, and liver. Mutations in the telomerase reverse transcriptase and telomerase RNA component genes have been observed at a higher prevalence in patients with liver disease compared with the general population; however, the presence of variants in other components of the telomerase complex and their impact on clinical outcomes has not been explored. We evaluated 86 patients with end‐stage liver disease for variants in an expanded panel of eight genes, and found that 17 patients (20%) had likely deleterious variants by in silico analysis. Seven unique likely deleterious variants were identified in the regulator of telomere elongation helicase 1 ( RTEL1 ) gene that encodes for a DNA helicase important in telomere maintenance and genomic stability. In gene burden association analysis of their clinical data, the presence of any RTEL1 variant was associated with a 29% lower baseline white blood cell count (95% confidence interval [CI], ‐7% to ‐46%; P Value = 0.01) compared with patients without RTEL1 variants, and the presence of any exonic missense RTEL1 variant was associated with a 42% lower baseline platelet count (95% CI, ‐5% to ‐65%: P Value = 0.03). The presence of any telomerase variant was associated with an increased number of readmissions within 1 year after transplantation demonstrated by an incident rate ratio (IRR) of 3.15 (95% CI, 1.22 to 8.57). No association with survival was observed. Conclusion : Among patients who underwent liver transplantation, the presence of any exonic missense variant was associated with a longer postoperative length of stay with an IRR of 2.16 (95% CI, 1.31 to 3.68).